Diagnosing the level of aesthetic education of preschool children (Czech Journal of Multidisciplinary Innovations, 2022)
based on the analysis of scientific sources for the study of the aesthetic development of older preschool children, the essence and importance of the aesthetic development of children is revealed, the signs of the aesthetic development of the individual are shown schematically, the criteria and indicators of the aesthetic development of preschool children are developed. The article analyzes the level of aesthetic development of older preschool children - students of the city budget preschool educational institution.